Virtual voice assistant applications improved expressive verbal abilities and social interactions in children with autism spectrum disorder: a Single-Subject experimental study - Safi, Mohammed F.; Al Sadrani, Badriya; Mustafa, Ashraf (International journal of developmental disabilities, 2023)
The use of interactive technologies has been demonstrated to enhance verbal and non-verbal communication, as well as the social interaction tendencies of children with Autism Spectrum Disorder (ASD). We examined effects of using Virtual Voice Assistant (VVAs) in children with ASD with respect to two outcomes: speech skills and social interaction skills. A single-case study included three children with ASD (4-11 years old) that utilized VVAs for three months. Pre- and post-intervention questionnaires and semi-structured interviews were used to measure the communication and social interaction skills of the participating children. Participant One, Two and Three showed improvement in the number of correct words produced the VVA intervention. All participants showed increases in social interactions in the intervention phase. Overall, the results showed that the VVAs had positive effects on the speech and social interaction skills of autistic children. The findings demonstrate that children with ASD may benefit from VVAs to improve their communication skills.